Parenting priorities and pressures: furthering understanding of 'concerted cultivation'. Issue 2 (3rd March 2016) - Vincent, Carol; Maxwell, Claire
Abstract : This paper re-examines the purposes of a planned and intentional parenting style – 'concerted cultivation' – for different middle-class groups, highlighting that social class fraction, ethnicity, and also individual family disposition, guides understandings of the purposes of enrolling children in particular enrichment activities. We examine how parents and their children engage in extra-curricular activities for instrumental reasons with a view to securing skills, qualities and distinction for the future. Additionally, however, enrichment activities are understood as offering present-day values such as enjoyment, social bonding and purposeful activity. The paper also highlights that current policy and broader commercial discourses call for the increased responsibilisation and intensification of parenting, which means that 'good' parents are required to 'buy into' extra-curricular activities for their children, with concomitant implications for those whose access to activities is limited by economic circumstance.